Characterization and Energy Densification of Agroindustrial Residues Blends - Silva, Nicole C. [UNESP]; De Conti, Claudio [UNESP]; Padilla, Elias Ricardo D. [UNESP]; De Conti, Andrea C. [UNESP] (Soc Brasileira Quimica, 2021)
The production of briquettes with different proportions of biomass presents an alternative for energy purposes, making the logistics of the process and increasing its efficiency viable. In this sense, the present work aimed at the energetic characterization of raw cassava rhizome (CM), bagasse (BC), and sugar cane straw (PC) blends. Four blends with different proportions of biomass were determined, based on 270 g of total residues, as follows: blend I (66.66% CM, 16.67% BC and 16.67% PC), blend II (16.67% CM, 16.67% BC and 66.66% PC), blend III (33.33% CM, 33.34% BC and 33.33% PC) and blend IV (16.67% CM, 66.66% BC and 16.67 PC). We did the material's chemical characterization through the immediate analysis, following the norms ASTM-D3174 and ASTM-D3175. Twelve briquettes were produced for each blend, with 42 mesh granulometry, through energy densification. We used a manual hydraulic press exerting a 10 tons-force and pressing time of 60s. For 72 hours, we did the volumetric expansion. Blend I presented better performance among all the blends, showing 13.13% for fixed carbon, 5,841.69 kcal.kg(-1) for PCS, 5,544.93 Mcal/m(3) for energy density, 1.251 MPa for mechanical resistance, respectively. All the blends presented optimal stacking conditions. The smallest volumetric expansion occurred in the blend I briquettes produced, showing a result of 7.06%. We found that adding cassava strain to the briquettes caused the briquettes to have a lower friability index. Therefore, it follows that the cassava starch in the raw cassava rhizome acted as the natural binder of the residue.
Keywords: Biomass; energy density; mechanical strength; strain in cassava